Holocene Environmental Dynamics of the Lago Cochrane/Pueyrredon Valley, Central West Patagonia (47°S) - Maldonado, Antonio; de Porras, Maria Eugenia; Martel-Cea, Alejandra; Reyes, Omar; Nuevo-Delaunay, Amalia; Mendez, Cesar (My University, 2022)
Deglaciation modeling of the Patagonian Ice Field since the Last Glacial Maximum has been a topic of intensive research in Central West Patagonia (44 degrees-49 degrees S). However, the chronology of deglaciation onset, acceleration, and the subsequent thinning and recession of the different ice lobes as well as the timing and extension of large proglacial systems are still a matter of discussion. The maximum eastward extension the Lago Cochrane/Pueyrredon ice lobe was around similar to 20,000-27,000 cal yrs BP; its associated proglacial lake drained toward the Pacific between 12,600 and 8,000 cal yrs BP. This study presents the first two pollen and charcoal records from the Lago Cochrane/Pueyrredon valley, spanning the last 11,650 cal yrs BP. The Laguna Maldonado record spans between 11,650 and 8,500 cal yrs BP, while the Laguna Anonima record the last 8,500 cal yrs BP, thereby overlapping chronologically. The lithological record of Laguna Maldonado shows that organic sedimentation began at the onset of the Holocene (11,650 cal yrs BP), once the site was free of glacio-lacustrine influence. Between 11,650 and 10,500 cal yrs BP, an open Nothofagus forest developed associated with high fire occurrence/frequency, followed by a transitional phase to a closer forest associated with a shift from low to high fire activity up to 9,400 cal yrs BP. Between 9,400 and 8,500 cal yrs BP, the Laguna Maldonado record suggests the development of an open forest or probably scattered patches of forest of variable size in a steppe matrix, probably related to geomorphological and paraglacial dynamics as well as climatic forcings, while the Laguna Anonima record indicates the development of a closed Nothofagus forest and high to low fire occurrence/frequency from 8,200 to 3,800 cal yrs BP. Since 3,800 cal yrs BP, a highly dynamic open forest or forest patches scattered in a grass/shrub-grass steppe matrix occurred around Laguna Anonima associated with high fire occurrence/frequency synchronous with an important increase in the presence of hunter-gatherers during the last 3,000 years. The results from the Lago Cochrane/Pueyrredon valley are integrated and discussed at the regional scale alongside other records from Central West Patagonia.
Keywords: holocene; pollen records; human-environment interaction; environmental dynamics; central west patagonia